A guide to selecting high-performing antibodies for VAPB (UniProt ID: O95292) for use in western blot, immunoprecipitation, and immunofluorescence [version 1; peer review: 3 approved, 1 approved with reservations] - Maryam Fothouhi; Peter S. McPherson; Carl Laflamme; Sara González Bolívar; Riham Ayoubi; Charles Alende; Irina Shlaifer (F1000Research)
VAPB is an adaptor protein known for its role as an anchor for other proteins at the endoplasmic reticulum. A mutant form of VAPB has been linked to amyotrophic lateral sclerosis and the underlying mechanisms resulting from this defect are studied by researchers in this area to uncover its implication in the disease. Here we have characterized six VAPB commercial antibodies for western blot, immunoprecipitation, and immunofluorescence using a standardized experimental protocol based on comparing read-outs in knockout cell lines and isogenic parental controls. These studies are part of a larger, collaborative initiative seeking to address antibody reproducibility issues by characterizing commercially available antibodies for human proteins and publishing the results openly as a resource for the scientific community. While use of antibodies and protocols vary between laboratories, we encourage readers to use this report as a guide to select the most appropriate antibodies for their specific needs.